ФОРМУВАННЯ КУЛЬТУРИ ПЕДАГОГІЧНОГО СПІЛКУВАННЯ МАЙБУТНІХ УЧИТЕЛІВ У КОНТЕКСТІ ПЕДАГОГІЧНИХ ТЕХНОЛОГІЙ (Педагогіка вищої та середньої школи, 2010)
The author emphasizes the necessity of using the pedagogical technology as an effective means of formation the culture of pedagogical communication of future teachers.